Membongkar penyelewengan mencari kebenaran karya pemenang Anugerah Kajai, hadiah kewartawanan Malaysia MPI Petronas, 1980-2011 (Media Global Matrix, 2012)
News writing on various issues happening in Malaysia; prize winning articles of the Kajai Award from 1980 to 2011, the highest accolade for journalists in Malaysia